CYBER NOTARY MENJADI SOLUSI PROBLEMATIKA PERJANJIAN ENDORSEMENT - Prihantiwi, Lidwina Tessa Kurnia (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This article aims to identify the issues arising from endorsement agreements made without a Notarial Deed and analyze why many endorsers and endorsees prefer to make such agreements without a Notarial Deed, despite the potential legal problems that may arise. Additionally, the article proposes solutions to address these issues. This study employs a normative juridical approach with a prescriptive nature. The data used are secondary, collected through document and literature studies, with analysis conducted using a deductive method. The research findings reveal two main issues stemming from endorsement agreements made without a Notarial Deed: violations of the principle of freedom of contract and the potential use of such agreements for money laundering purposes. The reasons endorsers and endorsees prefer agreements without a Notarial Deed include the desire for a quick and practical process, while creating an agreement with a Notarial Deed is more time-consuming. Despite the potential issues, such as standardized agreements and the risk of money laundering, endorsers and endorsees continue to choose agreements without a Notarial Deed. To address these issues, the implementation of Cyber Notary is needed in the endorsement agreement process.